THE ELECTION CONFLICT OF MANDAILING TRIBE LEADER: AN ANALYSIS ON VICTIMOLOGY - Kasmanto Rinaldi (Bajang Institute, 2022)
In the study of victimology, it was explained that some of community members tended to be repeatedly victims of crime. So, as long as there is no recovery carried out regarding this problem, the community is described as continuing victimization. This happened in Sei Kumango Village, Sub-distric Tambusai, Rokan Hulu Regency, Riau Province. There is a confilct about the election of the Mandailing tribe leader in that village, and it made the community be in a very disadvantaged situation. Through qualitatives research approach, this research explained the conflict that occurs causes an adverse impact on the community in a psychological aspect and cultural aspect that exist in the community itself. In victimology, that problem is described as a form of Politically Victims, that is those who suffer because of their politic oponnent where it was explained that the conflict’s impact which had afflicted the community in both camps was an impact that occurred because of the leader election. Indirectly, the community became political victims of leader’s election in Mandailing tribe, Sei Kumangi village.